HIERARCHY OF NEEDS IN DAN GILROY’S NIGHTCRAWLER - Kusuma, Ricky Nugraha (LANTERN (Journal on English Language, Culture and Literature), 2016)
Nightcrawleris a crime-thriller movie directed by Dan Gilroy. The movie is about an ambitious videographer who sells violent footage of accidents and brutal crimes to the local news TV. The focus of this study is to analyze the motivation of Louis Bloom, the main character in the movie, using Abraham Maslow’s theory of needs. This theory is illustrated in a shape of five layered pyramid which represents every need that must be fulfilled by human. Those needs are physiological needs, safety needs, love or belongingness needs, esteem needs, and self-actualization needs. The result of the discussion shows the five phases of theory of needs reflected in Lou’s life.